CADANGAN KARBON PADA TEGAKAN KARET DI PERKEBUNAN LAMANKUYANG SEBAGAI SUMBER BELAJAR PADA MATERI PENCEMARAN UDARA BIOLOGI SMA - Riski, Samsul; Wulandari, Sri; Firdaus, L.N. (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Rubber stands as natural carbon reserves need to be explored and it is considered important to be developed by teachers as a source of contextual learning that is relevant to current natural phenomena. This study aims to produce learning resources in the form of a design of the High School Biology learning module based on carbon stock estimation as air pollution mitigation. For this reason, research has been carried out at the Lamankuyang rubber plantation to obtain scientific data and information as module design material through a partially developed research method (Analysis and Design stage). Determination of the location of the study was carried out by stratified sampling technique. Sampling is carried out by non-destructive strip transect method. Data from the subsequent research will be analyzed using the allometric formula to determine the value of contained biomass and carbon stock. The results show that the rubber stand value of carbon reserves is 73.5 tons / ha with carbon absorption of 1349.8 tons / ha. The factors that influence include diameter, age, clones, spacing and environmental conditions. All research data can be used to design the Class X Air Pollution Mitigation Module for High School Biology Subjects using the Problem-Based Learning Model. However, before the module design is used on a broader scale, it is recommended that a feasibility and effectiveness test be carried out on a limited scale.Key Words: High School Biology Learning Module, Air Pollution Mitigation, Rubber Stand,Lamankuyang Plantation